Pemberdayaan Keagamaan Jamaah Mushalla Uswatun Hasanah, Desa Kayu Bongkok, Kabupaten Tangerang: Religious Empowerment of the Congregation at Mushalla Uswatun Hasanah, Kayu Bongkok Village, Tangerang Regency - Ulfah Zakiyah; Muhammad Ghifari; Putri Rachmah A. (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This community service activity was conducted at Mushalla Uswatun Hasanah, Kayu Bongkok Village, Sepatan Subdistrict, Tangerang Regency, focusing on mentoring the recitation of Ratib al-Haddad integrated with religious discussions on supplication (du‘a) and prayer (salat). The main issue faced by the community was the limited understanding of the meaning and content of Ratib al-Haddad, as well as the lack of integration between collective dhikr practices and reflective understanding of prayer and supplication in daily religious life. This program aimed to strengthen the community’s religious understanding, improve the quality of worship practices, and enhance the role of the mushalla as a center for community-based religious development and empowerment. The activity employed a participatory approach, including preliminary observation, collective recitation of Ratib al-Haddad, short religious lectures, interactive discussions, and qualitative evaluation. The results indicate an improvement in participants’ understanding of dhikr, supplication, and prayer, increased enthusiasm and participation among congregants, and strengthened social cohesion, particularly through the active role of women as key drivers of religious activities. Furthermore, the program encouraged the sustainability of religious practices managed independently by the congregation and mushalla administrators. Overall, this community service demonstrates that mentoring religious traditions rooted in local practice can serve as an effective instrument for spiritual and social empowerment within the community.